Random sequence analysis of genomic DNA of a hyperthermophile: Aquifex pyrophilus - Choi, IG; Kim, SS; Ryu, JR; Han, YS; Bang, WG; Kim, SH; Yu, YG (SPRINGER VERLAG, 1997)
Aquifex pyrophilus is one of the hyperthermophilic bacteria that can grow at temperatures up to 95 degrees C. To obtain information about its genomic structure, random sequencing was performed on plasmid libraries containing 0.5-2kb genomic DNA fragments of A. pyrophilus. Comparison of the obtained sequence tags with known proteins revealed that 123 tags showed strong similarity to previously identified proteins in the PIR or Genebank databases. These included three proteases, two amino acid racemases, and three enzymes utilizing oxygen as substrate. Although the GC ratio of the genome is about 30%, the codon usage of A. pyrophilus showed biased occurrence of G and C at the third position of codons, especially those for amino acids such as asparagine, aspartic acid, cysteine, glutamine, glutamic, acid, histidine, lysine, and tyrosine. A higher ratio of positively charged amino acids in A. pyrophilus proteins as compared with proteins from mesophiles suggested that Aquifex proteins might contain increased ion-pair interaction that could help to maintain heat stability.
Keywords: NUCLEOTIDE-SEQUENCE; GEN-NOV; DEHYDROGENASE; BACTERIA; PROTEASE; ENZYME